If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x-9=12x-1
We move all terms to the left:
7x-9-(12x-1)=0
We get rid of parentheses
7x-12x+1-9=0
We add all the numbers together, and all the variables
-5x-8=0
We move all terms containing x to the left, all other terms to the right
-5x=8
x=8/-5
x=-1+3/5
| 6x+18=12x–6 | | 6x+18=12x–6. | | 1/x=0.054 | | (x-2)/4-(x-3)/3=1/2x+1 | | y=1/2+-4 | | 0.7x-4=0.2x+6 | | 17+m=35 | | 4(x+1)=3(x+5) | | 8x-10=22-x | | x/3+5=2x-14 | | x^2+2.4x+2.4=0 | | n^2+3n-7=21 | | n^2-3n+7=25 | | d+5=5+d | | -2+-4x=-4+18x | | n^2-3n+7=2 | | n^2-3+7=24 | | n^2-3+7=25 | | n^2-3+7=21 | | 4x+5=2x- | | 3-4x=5-7x | | -7x-5=-9x+1 | | n^2-2n-5=19 | | -7x-5=-9x | | n^2-5n+2=47 | | x+2(3x+1)=3(x-2 | | 6x-6=36x+4 | | -13+2x=-52+23x= | | 7x+4=-2=40 | | 4y-6(-2.5)=23 | | x=-2.5,46-6x=23 | | 4x2+5=2x+1 |